Mechanisms of Cell Damage and Protection in Ischemia/Reperfusion and Experimental Rationale for the Use of Lithium-Based Preparations in Anesthesiology - V. V. Moroz; D. N. Silachev; E. Yu. Plotnikov; L. D. Zorova; I. B. Pevzner; O. A. Grebenchikov; V. V. Likhvantsev (Общая реаниматология, 2013)
Pharmaceuticals based on lithium ions have been already used in clinical practice for over 60 years for the treatment of bipolar disorders and remain a basic pharmacological therapy for patients with this disease. In spite of this, the therapeutic mechanisms of action of lithium ions have not been fully investigated. In the past decade, in vitro and in vivo experiments have provided a good deal of data suggesting that lithium ions have previously undescribed neuro-, cardio-, and nephro-protective properties. Numerous investigations have demonstrated that glycogen synthase kinase-3/3, the key enzyme of different pathological and protective signaling pathways, is the target of lithium ions in displaying these effects. This review deals with just these new properties of lithium ions, which make them utterly promising for clinical use in circulatory arrest-associated conditions, which is particularly relevant for anesthesiology and resuscitation. Key words: lithium ions, brain, heart, kidney, postresuscitation disease.